The Shifting Structure of China's Trade and Production - Cui, Li (IMF Working Papers; Working Paper ;, 2007)
This paper uses disaggregated trade data to assess how the expansion of China's production capacity and its changing production structure may be affecting its trade linkages with other countries. It finds that China is moving away from traditional assembly operations in its processing activities and its exports have started to rely more on domestically sourced components. In turn, China's imports and exports have begun to delink, with increased domestic sourcing contributing to the recent increase in its trade balance. In addition, as China moves up the value chain, both its imports and exports have become more sophisticated than in the past. As a result of these shifts, China may be becoming more exposed to fluctuations in the strength of the global economy, and changes in its exchange rate could have a bigger impact on the trade balance and the domestic economy than commonly believed.